(untitled) (Damascus University Journal of agriculture sciences, 2024)
This research was conducted in Western Zahed station in Tartous during the agricultural season (2019), to study the impact of deficit irrigation in Sesbania plant productivity by using three water treatments: full irrigation, 75% of full irrigation, and 60% of full irrigation, the experiment was designed by full random sectors method, drip irrigation method was used. Watering process happened when soil moisture reached to 80% of field capacity, and continued until 100% of field capacity in the full irrigation treatment, 75% of full irrigation, and 60% of full irrigation treatments were provided in 75% and 60% of water that the full irrigation treatment was provided in, respectively. The full irrigation and 75% of full irrigation treatments achieved the highest average yield 12500 Kg/ha and 10433 Kg/ha, respectively, while there was no significant differences in the water use efficiency between all treatments.